Diffuse Axonal Injury and Cerebral Contusions on MRI Are Associated with Decreased Functional Outcome in CT-negative TBI: A TRACK-TBI Pilot Study. (16th November 2020) - Yue, John K; Yuh, Esther; Stein, Murray; Winkler, Ethan; Deng, Hansen; Dalle Ore, Cecilia L; Vassar, Mary; Taylor, Sabrina; Schnyer, David; Lingsma, Hester F; Puccio, Ava; Mukherjee, Pratik; et al.
Abstract: INTRODUCTION: Intracranial pathology on MRI after traumatic brain injury (TBI) is heterogeneous, and prior studies have shown associations between contusions, axonal injury and poorer 3-month outcome. METHODS: CT- TBI subjects from the prospective Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot (TRACK-TBI Pilot) who completed a 2-week research MRI and 6-month Glasgow Outcome Scale-Extended (GOSE) were included. GOSE was dichotomized to good recovery (7-8) vs. moderate disability or worse (<7). MRIs were scored according to NINDS Common Data Elements by a central board-certified neuroradiologist, and included traumatic axonal injury (TAI, 1–3 foci of shear) and diffuse axonal injury (DAI, >3 foci of shear). Odds ratios (OR) and [95% confidence intervals] are provided. RESULTS: In 108 CT- subjects, 29% were MRI+ (18% TAI-only, 4% DAI-only, 3% subdural hematoma (SDH)-only, 2% TAI + Contusion, 2% DAI + Contusion + SDH, 1% Contusion-only). Subjects were aged 36.8 ± 14.9 years, 31% male, 72% Caucasian, with mean GCS 14.6 ± 1.4, and 40% were admitted to hospital, which did not differ by MRI+/−. At 6 months postinjury, 32% had moderate disability or worse (GOSE < 7),  which did not differ significantly by MRI+/− but differed by DAI+/− and Contusion +/− on subgroup analyses (MRI−: 28.6%, MRI+ without DAI/Contusion: 27.3%, DAI+: 80%, Contusion+: 60%). The combined DAI/Contusion + group was more likely to have GOSE < 7 compared to those without DAI/Contusion (66.7% vs. 28.3%, OR = 5.07 [1.19-21.69]). CONCLUSION: In a cohort of TBI patients with negative initial head CT, presence of DAI and contusion on MRI was associated with significantly worsened 6-month clinical outcomes. MRI in acute TBI may be a more sensitive assessment tool for predicting persistent functional disability.